The Debate of Change and Continuity in Trump’s Foreign Policy - Sidra Khan (ASIAN Journal of International Peace & Security (AJIPS), 2021)
Trump’s foreign policy outlook and rhetorical predispositions indicate that American foreign policy has undergone significant changes in terms of substance. The arrival of Trump at the helm of affairs had created a conventional perception of a gradual retreat by the United States from liberal internationalism. The Trump administration relied heavily on Jacksonian foreign policy to seek alternative ideas for reinterpreting the United States’ role in the current international order. Such a foreign policy pursuit resulted in the rise of A-moral transnationalism, an approach that called into question several key pillars of US international engagement in order to gain short-term economic gains. To that end, this article will examine theoretical and historical aspects of US foreign policy, as well as policy practices implemented by the Trump administration during his four years in office, in order to test claims of continuity or transformation in US foreign policy.